An update on recently approved long-acting injectable second-generation antipsychotics: Knowns and unknowns regarding their use - Amy M. VandenBerg, PharmD, BCPP (American Association of Psychiatric Pharmacists, 2022)
There are now 9 available FDA-approved second-generation long-acting injectable antipsychotics including aripiprazole (3), olanzapine (1), paliperidone (3), and risperidone (2). These high-cost medications are commonly used with the goal of improving adherence and patient outcomes. With almost 2 decades of use, key aspects have been well studied, including population pharmacokinetics, CYP interactions and various clinical and economic outcomes. However, there are still unknowns with these medications. Issues including adherence, transition from oral antipsychotics, renal dosing, pharmacogenomics, and managing missed doses will be addressed in the context of 4 patient cases.